DEIXIS ANALYSIS USED IN PAMUNGKAS SONG LYRICS ENTITLED “PLEASE BABY PLEASE” - Wayan, Suarjana Putra (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2024)
This research focuses on analysing deixis contained in Pamungkas' song Please Baby Please. Deixis is one of the essential things that humans do by speaking, known technically as "deixis" (from Greek). Through language, this means "pointing". Deixis is usually used to analyze conversations, speeches, song lyrics, movie scripts, etc. This research has two objectives; the first is to analyze the types of deixis contained in Pamungkas' song Please Baby Please and analyze the context of the situation contained in the song. Deixis determines who, to whom, and where a reference is made. Person deixis, spatial deixis, temporal deixis, social deixis, and discourse deixis are some deixis forms that refer to the theory of Cruse (2000). This research uses the qualitative method, where the qualitative method is used to describe the types of deixis found in Pamungkas' song. The total deixis data found in this study amounted to 14 data, of which the number of each primary data, where persona deixis amounted to five data (38.7%), then followed by temporal deixis as much as four data (28.5%), followed by spatial deixis as much as three data (21.4%), and social and discourse deixis showed the same result, namely one data (7.1%).